Peripheral reaching in Alzheimer's disease and mild cognitive impairment. (April 2022) - Mitchell, Alexandra G.; Rossit, Stephanie; Pal, Suvankar; Hornberger, Michael; Warman, Annie; Kenning, Elise; Williamson, Laura; Shapland, Rebecca; McIntosh, Robert D.
Abstract: Recent evidence has implicated areas within the posterior parietal cortex (PPC) as among the first to show pathophysiological changes in Alzheimer's disease (AD). Focal brain damage to the PPC can cause optic ataxia, a specific deficit in reaching to peripheral targets. The present study describes a novel investigation of peripheral reaching ability in AD and mild cognitive impairment (MCI), to assess whether this deficit is common among these patient groups. Individuals with a diagnosis of mild-to-moderate AD, or MCI, and healthy older adult controls were required to reach to targets presented in central vision or in peripheral vision using two reaching tasks; one in the lateral plane and another presented in radial depth. Pre-registered case–control comparisons identified 1/10 MCI and 3/17 AD patients with significant peripheral reaching deficits at the individual level, but group-level comparisons did not find significantly higher peripheral reaching error in either AD or MCI by comparison to controls. Exploratory analyses showed significantly increased reach duration in both AD and MCI groups relative to controls, accounted for by an extended Deceleration Time of the reach movement. These findings suggest that peripheral reaching deficits like those observed in optic ataxia are not a common feature of AD. However, we show that cognitive decline is associated with a generalised slowing of movement which may indicate a visuomotor deficit in reach planning or online guidance.